Stimulation of child's sexual imitation behavior through Neurolinguistic programming - Edhy Rustan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study aims to determine the forms of child sexual imitation behavior, influencing factors and the role of parents and teachers in addressing the sexual imitation of children. This type of research is descriptive qualitative research using direct observation and interview methods as research data sources. The results of this study indicate that children engage in sexual imitation in the form of sexual movements. This behavior is caused by errors in parenting. Parenting is too permissive so that it does not allow the child to sleep alone as a result the child sees his parents having sexual relations and imitates them when playing or studying at school. In dealing with these behaviors, a Neurolinguistic Programming (NLP) approach can be used where parents play a role in training the independence of children by (1) creating a pleasant atmosphere for children (2) giving positive suggestions through fairy tales. While in school teachers provide positive education and suggestions through learning programs in schools by integrating sexual education into the appropriate learning themes.